Association of Helicobacter Pylori Infection with HIV positive patients - alireza abdollahi; saeed shoar; siroos jafari; hamid emadi-kochak (Mediterranean Journal of Hematology and Infectious Diseases)
The aim of this study is to assess the prevalence of H. pylori infection among HIV positive patients in Iran. We also evaluated the type of anti bodies and its titer among H. pylori infected cases.A group of 114 AIDS positives and as many healthy people underwent examination for anti-helicobacter pillory antibodies, the number of CD4-positive lymphocytes as well as other blood-related parameters.